To Honor Jerald C. Brauer - Marty, Martin E. (Church history, 1991)
It is not easy to edit an issue of a journal without the knowledge or participation of one of the two coeditors. But the editorial assistants, special editor, and I have done just that in the case of Jerald C. Brauer. He turns seventy late this summer, and in the name of the American Society of Church History, its Council, and the editorial advisory council of Church History and its staff, we dedicate this issue to him. Members of the Society and readers of this journal will be glad to hear that the Council asked him to remain in his coediting post and named him to another term.